Synthesis, characterization and electrochemical properties of isoflavone substituted zinc(II), cobalt(II), and metal-free phthalocyanines - (:unkn) unknown (WORLD SCI PUBL CO INC, 2019)
In this study, novel tetrasubstituted metallo- and metal-free phthalocyanines containing 7-hydroxy-4'-methoxyisoflavonoxy moieties at peripheral and non-peripheral positions have been prepared by cyclotetramerization of corresponding phthalonitriles. The most obvious feature of these quaternized complexes is their extensive solubility and non-aggregated species (especially non-peripherally substituted) in organic solvents such as chloroform, tetrahydrofuran, dimethylformamide and dimethylsulfoxide, which makes them candidates for use in many applications in different fields. The new compounds have been characterized by elemental analysis, FF-IR, UV-vis, H-1 and C-13 NMR and MS (Maldi-TOF MS). Voltammetric and in situ spectroelectrochemical measurements have been performed with the aim of characterizing the electron transfer properties of the compounds on Pt in dimethylsulfoxide/tetrabutylanunonium perchlorate, compared to those of previously reported corresponding compounds with tetra 6-hydroxyflavonoxy substituents. The effect of aggregation on the redox character of these complexes was also discussed.
Keywords: phthalocyanines; isoflavone; electrochemistry; spectroelectrochemistry; SPECTROELECTROCHEMICAL CHARACTERIZATION; COPPER PHTHALOCYANINE; BEARING COUMARIN; REDUCTION; COMPLEXES; ACID; MANGANESE; SENSOR